High prevalence of metabolic syndrome in patients with SLE in the Western Cape - Nkabane, Avela Ntombenkosi (Department of Medicine, 2021)
INTRODUCTION: Patients with systemic lupus erythematosus (SLE) are at increased risk of the metabolic syndrome (MetS) and its complications. In the absence of published studies from sub-Saharan Africa, we investigated the prevalence and associations of the MetS amongst recent-onset SLE patients. METHODS: A cross-sectional study of recent onset (<5 years disease duration) patients with SLE meeting the SLICC SLE classification criteria. The MetS was defined by Joint Interim Statement criteria. Clinical and demographic data and a Functional Assessment of Chronic Illness Therapy score and the 36-Item Short-Form Healthy Survey were completed. RESULTS: Of 75 patients, the mean age was 37.1 (11.7) years, disease duration was 30.8 (23.6) months, 65 (86.7%) were female, 68.0% were of mixed ethnic ancestry and 29.3% were Black Africans. The mean SLEDAI score was 0.9 (1.6). The prevalence of MetS was 40.0%, and age and body mass index were the only significant features associated with MetS (p = 0.003 and 0.001 respectively). Increased waist circumference (WC) was the most frequently observed feature, present in 92.9% of MetS patients. Patients with an elevated WC were 32.5 times more likely to have MetS. CONCLUSION: This study shows a high prevalence of MetS amongst South Africans with recently diagnosed SLE. This calls for aggressive strategies to reduce the prevalence of Mets and atherosclerotic cardiovascular disease. Waist circumference is a useful and costeffective screening tool to identify SLE patients at risk of MetS.